(untitled) (Heritage, 2022)
The aim of this paper is to find out whether the quality of educator’s instruction impact the manifestation of creativity in preschool children. The study involved 100 children aged between 5 and 6 years, who were divided into two equal groups. According to the research, A4 paper was used on which there was a drawn triangle. The educators instructed the first group of children: "Finish this drawing", while the second group of children was instructed: "Complete this drawing correctly". A team of experts composed of researchers, pedagogues, educators and art teacher evaluated the drawings according to the following characteristics: number of lines, number of colors used, number of objects in the drawing and composition of the drawings. Each of the three evaluators chose drawings that he considered creative. Statistically significant difference found in the number of colors, lines and objects used The results showed that there are no statistically significant differences between the two groups given the complexity of the composition of the drawings. Statistically significant differences no found in the number of drawings marked as creative by different evaluators. Based on the analysis conducted in this research, it can be concluded that preschool children express their creativity freely and naturally, regardless of the instructions of the educator. Given that previous research has confirmed that creativity is stifled by starting primary school, it is necessary to find and describe the causes that lead to it, and in accordance with future findings to create new paradigms that will be the basis of holistic child development.